The Social Influence Of Family Support And Long Suffering On Self Management In Type 2 Diabetes Mellitus (DM) Patients At Gotong Royong Hospital Surabaya: Cross Sectional Study - Zulkarnain, Eva Vera; Abdul Muhith; Siti Nur Hasina (Journal for Quality in Public Health, 2024)
Introduction. Lack of awareness of type 2 DM patients and the duration of suffering are factors that inhibit type 2 DM sufferers from carrying out self-management properly. The purpose of this study was to determine the effect of family support and long suffering with self-management in patients with Diabetes mellitus (DM) type 2. Methods. The study design used cross sectional. The population is patients with type 2 diabetes mellitus. The total sample was 167 respondents, taken according to inclusion and exclusion criteria. The sampling technique used is purposive sampling. The independent variables are family support and long suffering. The dependent variable is self-management. Data was collected using questionnaires that have been tested for validity and reliability using product moments. The data were analyzed using spearman rho analysis. Results. The results showed that there was an association of family support for self-management (p = 0.000) and no association of long suffering with self-management diet (p = 0.879). Discussion. High family support can make people with type 2 DM have good self-management. long suffering from DM does not necessarily make DM sufferers have good self-management. As long as people with type 2 DM have the awareness to carry out self-management well, complications can be prevented. For health workers, it is expected to further optimize health education and counseling in increasing spiritual intelligence in carrying out self-management of type 2 DM.